(untitled) (مجلة إحالات, 2026)
This paper is an attempt to find out the aesthetic phenomenon in its conceptual dimension that is close to its actual existence on the basis of its physical embodiment after starting from its theoretical concepts, and this research is related to the creative aspect as it is related to the critical space associated with creative poetic works in particular. This attempt is related to the philosophy of poetic action as well as critical one as it relates to the relationship of the poet to the poetic word that moves on a margin of tow sides: are clarity and ambiguity, which are the two concepts associated with the daily use of the word, just as they are related to the personal written experience of the poet.